The Association of A Number of Predictive Factors for The Recurrence of Papillary Urothelial Neoplasm of Low Malignant Potential: Prognostic Analysis From Multiple Academic Centers - Kim, Ki Hong; Lee, Seung Hwan; Kim, Sun Il; Chung, Byung Ha; Koo, Kyo Chul; Cho, Jin Seon; Bang, Woo Jin; Park, Jong Yeon; Hong, Sung Joon (Urology Journal, 2019)
Purpose: To identify clinically useful predictors for the recurrence of papillary urothelial neoplasm of low malignant potential (PUNLMP), we reviewed the clinical information of patients who were diagnosed and treated in multiple tertiary-care academic facilities. Materials and Methods: Between February 2007 and April 2015, 95 patients diagnosed with PUNLMP after transurethral resection of bladder (TURB) were included in this study. Age, gender, body mass index, smoking history, the presence or absence of previous history of urothelial neoplasm, the presence or absence of gross hematuria, cytological results at the time of diagnosis, tumor diameter, and multiplicity of tumor were estimated as variables for analysis. Cox regression tests were used for identifying predictive factors for recurrence of PUNLMP. Results: Sixty-nine cases of PUNLMP were de novo primary bladder PUNLMPs without known urothelial lesions in the urinary tract, and 26 PUNLMPs were identified on surveillance biopsies of patients with a previous history of urothelial neoplasm. During the follow-up period, recurrences developed in 13 patients (13.7%). Recurrence rates were 4.2% and 9.5% at 12 and 24 months, respectively. On univariate and multivariate Cox regression analyses, previous history of urothelial neoplasm [95% confidence interval (CI): 0.057-0.604, hazard ratio (HR) = 0.185, P = .005] and multiplicity of tumors [95% CI = 0.064-0.584, HR = 0.193, P = .004] were identified as independent predictors for recurrence-free survival of patients with PUNLMP. Conclusion: Tumor multiplicity and previous history of urothelial neoplasm are independent prognostic factors for prediction of recurrence of PUNLMP. More careful and closer follow-up should be recommended for PULNMP patients with tumor multiplicity or a previous history of urothelial neoplasm.